In vitro anticancer activity of ethanolic extract of Ipomoea marginata whole plant and leaves on breast cancer cell lines MDA-MB-231 and MCF-7 (International Journal of Food and Nutritional Sciences, 2022)
The morning glory family, Convolvulaceae, is extensively distributed in temperate, tropical, and subtropical areas. About 60 genera and nearly 1,600 species worldwide make up the convolvulaceae, which primarily twines plants or bushes and occasionally has milky sap. The purpose of the current investigation is to evaluate the anticancer potential of human breast adenocarcinoma (MCF-7) and mammary gland carcinoma (MDA: MB-231) cell lines in Ipomoea marginata. By using the MTT assay, the effects of ethanolic extract of I. marginata leaves and whole plants on the cancer cell lines MDA-MB-231 and MCF-7 were assessed. The results of the study showed that Ipomoea marginata's anticancer profile was efficient against MCF-7 cells, or human breast adenocarcinoma. According to the MTT experiment, whole plant incubation of cancer cell lines decreased the viability of the cancer cells, and the number of dead cells increased considerably with extract concentration. When compared to the leaves of